"Al Naqa" and its semantic fields in Lisan Al-Arab dictionary in the Structural Form of the Verb: Fa’auul - Badran, Loay Omar (Al-Adab Journal, 2022)
The Arabic language is characterized by many semantic fields and the Arabic language is also a contextual language which means it’s a broad language handling the linguistic expansion that other languages can’t handle. Based on these advantages of Arabic, this study is conducted to prove them by the selection of the semantic fields of "Al Naqa" adjectives in Arabic. ‏This study discusses the semantic fields of Al Naqa adjectives that are feminine without the usage of the feminine markers in the structural form of the verb "Fa’auul" in Lisan Al Arab dictionary, its widespread usage and the semantic field represented by that feminine semantics. More extensively, this study discusses two major topics, the introduction of the study is about the concept of femininity and its standardized markers that were set by professional Arabic language scholars and the literature review of the study discusses the semantic fields for the meanings of the unstandardized feminine adjectives which are without markers according to the structural form of the verb "Fa’auul". The importance of the study lies in its relations with many syntax and grammar lessons especially the indeclinable nouns, the diminutive pattern, plurals and so forth. Due to the fact that many Arabic speakers always mistake the description of masculinism and femininity especially the feminine semantics that don’t depend on the standardized feminine adjective with the feminine markers, the idea of this study comes out addressing the semantics of the structural form "Fa’auul" which is related to Al Naqa adjectives in particular and the attempt to classify these structures according to their accurate semantic fields.